Determinants of MyPertamina User Loyalty: A TAM-Mediated Model - Syifa Khoirunisa; Intan Annisa (Universitas Bumigora, 2026)
The rapid growth of digitalization in public services, including energy distribution systems, requires an in-depth understanding of the factors influencing user acceptance and loyalty. However, the implementation of the MyPertamina application still faces various user complaints related to system complexity, technical issues, and service inefficiency, indicating gaps between system expectations and the actual user experience. Integrating the Technology Acceptance Model (TAM), this study aims to an- alyze the effects of perceived ease of use and perceived usefulness on user loyalty toward the MyPertamina application in the Special Capital Region of Jakarta, with user satisfaction as a mediating variable. This research employs a quantitative approach using a survey method. The population consists of MyPer- tamina users, with a sample of 220 respondents selected through non-probability sampling. Data were collected using questionnaires and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS software. The results indicate that perceived ease of use and perceived usefulness have positive and significant effects on user satisfaction and user loyalty. In addition, user satisfaction significantly influences user loyalty and mediates the effects of perceived ease of use and perceived usefulness on user loyalty. The findings provide practical implications for improving digital service quality and enhancing the user experience to strengthen user loyalty.